Utilization of Digital-Based Interactive Stories in Indonesian Language Lessons as Innovative Media - Santi, Yulia; Dhani, Aulia; Juniman; Safrina; Fitriana; Fitri, Elly (Yayasan Citra Dharma Cindekia, 2024)
As an innovative learning media, the Utilization of Digital-Based Interactive Stories in Indonesian Language Lessons has become a necessity in the sophisticated learning process in this digital era. This article discusses the Utilization of Digital-Based Interactive Stories in Indonesian Language Lessons to improve student collaboration. This approach provides a solution to provide meaningful experiences for students with full involvement and student action and expression in Indonesian language lessons through strong visual and audio aspects as well as integrated challenges and rewards. Although digital-based interactive stories offer various benefits to motivate students in learning, their use in the classroom also faces challenges such as technology accessibility and integration into the curriculum. This article aims to explore more deeply the potential, challenges, and practical impacts of the use of digital-based interactive stories in improving the effectiveness of Indonesian language learning in the digital era. By understanding the importance of implementing this technology, comprehensive and in-depth research on this topic is needed to improve the quality of learning